Tumor‐Targeting Photothermal Heating‐Responsive Nanoplatform Based on Reduced Graphene Oxide/Mesoporous Silica/Hyaluronic Acid Nanocomposite for Enhanced Photodynamic Therapy. Issue 20 (10th August 2017) - Jiang, Wenjing; Mo, Fan; Jin, Xin; Chen, Lian; Xu, Liang Jun; Guo, Liangqia; Fu, FengFu
Abstract: This study herein develops a novel tumor‐targeting photothermal heating‐responsive nanoplatform for enhanced photodynamic therapy (PDT). The nanoplatform is prepared by using dopamine‐reduced graphene oxide nanosheets (rGO‐PDA) to enhance photothermal ability, mesoporous silica coated on the rGO‐PDA surface to load drug, and hyaluronic acid to act as gate keeper as well as targeting moiety. The developed nanoplatform has outstanding biocompatibility, well targeting ability, excellent near‐infrared radiation (NIR) photothermal conversion ability, controllable drug release with NIR irradiation response, and the capacity of delivering diverse drugs. The proposed nanoplatform is successfully used to specifically deliver chlorin e6 (Ce6) to CD‐44 over‐expressing cancer cells for PDT with a loading capacity of 0.605 mg mg −1 and controllable Ce6 release with NIR irradiation response. The combination of excellent NIR photothermal conversion ability and controllable Ce6 release confers the nanoplatform with enhanced singlet oxygen generation, which leads to more significant destruction of target cancer cells. The prepared photothermal heating‐responsive nanoplatform can enhance photodynamic therapeutic efficiency and hold great potential for multimodal cancer therapy. Abstract : A tumor‐targeting photothermal heating‐responsive nanoplatform, rGO‐PDA@MS/HA, is fabricated for enhanced photodynamic therapy of cancer with higher efficiency by employing rGO‐PDA to effectively adsorb near‐infrared radiation, MS to encapsulate drug, and HA to target the cancer cells and simultaneously to control the release of drug.